1, 2, 4‐Oxadiazole‐Based Bent‐Core Liquid Crystals with Cybotactic Nematic Phases. Issue 7 (3rd March 2014) - Shanker, Govindaswamy; Prehm, Marko; Nagaraj, Mamatha; Vij, Jagdish K.; Weyland, Marvin; Eremin, Alexey; Tschierske, Carsten
Abstract Several series of bent‐core mesogens derived from 3, 5‐diphenyl‐1, 2, 4‐oxadiazole with or without lateral groups and with different length terminal chains at both ends, and polycatenar molecules with three to six alkoxy chains are synthesized and their mesomorphic behaviour is investigated by polarizing microscopy, differential scanning calorimetry, X‐ray diffraction (XRD), dielectric, electro‐optical and second‐harmonic generation (SHG) experiments. Most compounds exhibit broad regions of skewed cybotactic nematic (NcybC) and tilted smectic (SmC) phases with a strong tilt of the aromatic cores (up to 63°), but non‐tilted SmA and NcybA phases are also observed for a compound that has only one terminal chain. The XRD patterns of the nematic phases of most of the compounds investigated indicate a 2D periodicity with short correlation length in the magnetically aligned samples. This is of importance for the general interpretation of the small‐angle XRD splitting patterns typically observed for aligned samples of bent‐core nematic phases. In most nematic phases one current peak is observed in the half period of an applied electric field, though no coherent signal is found in the SHG experiments. Based on additional electro‐optical and dielectric results, the nematic phases are considered to be cybotactic nematic phases with local polar order, and show a dielectric reorientation of the polar domains. Only chiral nematic phases (NcybC*), but not blue phases, are obtained for compounds with one or two chiral (3S)‐3, 7‐dimethyloctyloxy tail(s).